Development of cinnamon essential oil-loaded Pickering emulsions stabilized by chitosan/gelatin nanoparticles with enhanced antibacterial and antibiofilm actives - Zhilang Xu; Xinxin Wang; Huaqian Liang; Xinying Li; Derong Li; Changdao Mu; Liming Ge; Defu Li (Collagen and Leather)
Abstract Bacterial biofilm infection is a complicated and important global problem. Non-toxic biomass-based Pickering emulsions as an essential oil delivery system are a potentially effective means in biofilm treatment. Herein, the chitosan/gelatin complex nanoparticles (CGNPs) stabilized Pickering (CGP) emulsion loaded with cinnamon essential oil (CEO) was developed to inhibit and remove bacterial biofilms. CGNPs were initially successfully prepared with a particle size of 253.7 nm. Subsequently, CGP emulsions were prepared using CGNPs as the emulsifier and CEO as the oil phase, with the aqueous phase pH value of 5.5 and ionic strength of 50 mM. Amino groups of CGNPs were crosslinked with the aldehyde group of CEO via Schiff base reaction at the oil–water interface to form a denser core–shell structure, thus improving the stability of Pickering emulsion. The CGP emulsions exhibit controlled and long-term sustained release properties in essential oil delivery, with 89.8%, 81.0%, and 62.2% CEO release within 168 h for CGP-0.1, CGP-0.2, and CGP-0.3, respectively. Moreover, CGP emulsions have stronger antioxidant activities (nearly 100%), broad-spectrum antibacterial activities (> 90%), enhanced penetration and removal capabilities against preformed biofilms than single CEO or CGNPs, as well as its better biocompatibility than conventional surfactant-stabilized emulsions. Hence, CEO-delivered CGP emulsion could serve as a potential strategy against biofilm infections and bacterial resistance. Graphical abstract